Assessment of Cognitive Status of Elderly People Living in Nursing Homes in Larestan, 2018 - Hamed Delam; Esmaeil Kavi; Mohammad-Rafi Bazrafshan (Journal of Health Sciences and Surveillance System, 2019)
Background: Since the elderly  are more susceptible to cognitive impairment than other age groups, this study aimed to investigate the assessment of cognitive status of the elderly  living in nursing homes in Larestan city and the relationship between cognitive status of the elderly people and some demographic variables. Methods: This research was a cross-sectional study conducted on all the elderly living in a nursing home in Larestan city. Sampling was done by census method and 54 elderly people were selected according to the inclusion criteria. Demographic characteristics questionnaire was used to assess general information of the elderly, and standard mini mental state examination questionnaire was used to assess the elderly people’s cognitive status. Results: The mean age of the males was 69.44± 5.83 years with a range of 60-78. Mean and standard deviation of cognitive status were 25.28 ± 2.15 for males and 24.82 ± 2.54 for females, respectively. Also, 5 (9.30%) had moderate cognitive impairment, 24 (44.40%) had moderate cognitive impairment and 25 (46.30%) had normal cognitive status. There was a significant relationship between marital status and cognitive status in the elderly (p value = 0.012). The mean cognitive status of the married and single elderly was 24.10 ± 2.51 and 25.54 ± 2.13, respectively. Conclusion: Cognitive disorders are more prevalent among the elderly married couples, which can improve the adverse effects of these cognitive disorders by strengthening family relationships and caring.